URGENSI PENDIDIKAN ANAK USIA DINI DALAM ISLAM: Urgensi Pendidikan Anak Usia Dini - Sulhan Hamid A. Ghani (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
Children in the concept of Islam are blessing and gift from Allah; yet, not every couple is given this blessing. In addition, Islam also imparts that children are mandate from Allah, and then parents are suggested to guide, train and educate them. It is expected that children becomehuman being who are pious and spiritual in order to be reliable person for society, the nation, religion and the State. Furthermore, children are seen as the successor of the older generation in continuing the religious struggle in general, preaching and education in particular. Therefore, Islam obliges parents to give a good name, teach about faiths, worships and morals. Young children, a child who is between one to six years old, according to the concept of Islamic education, the development of the hidden abilities of the child through education known as early childhood education. The implementationof early childhood educationis expected to develop the potential in the physical, intelligence, social emotional, language and communication fields whose curriculum is adjusted to the development of the child's potential and endeavored so that children can learn while playing. This paper concludes that early childhood education has an important role because it will greatly influence the development of further educational abilities that the child will achieve.